The influence of different radiopacifying agents on hermetical sealing ability of calcium silicate and calcium aluminate dental cements - Ćetković Dejan; Zhiyu Cai; Vuković Nemanja; Vuković Zorica; Lei Huaxiang; Biočanin Vladimir; Huang Xiaojing; Jokanović Vukoman; Antonijević Đorđe; Dožić Aleksandra (Science of Sintering)
This study presents technological process for obtaining strontium enriched calcium silicate based dental ceramics and testing their microstructural and chemical properties. In brief, the influence of different radiopacifiers on microstructural properties of calciumsilicate (CaSi) and calcium-aluminate (CaAl) dental ceramics was evaluated. For synthesis of CaSi-based ceramics, calcium chloride pentahydrate (CaCl2⋅5H2O) and silica sol obtained by hydrothermal treatment were used. CaSi+barium-sulphate (BaSO4), CaSi + bismuth-oxide (Bi2O3), CaAl + zirconium-dioxide (ZrO2), CaAl + strontium-carbonate (SrCO3), CaAl+strontium-fluoride (SrF2), pure CaSi, pure CaAl and mineral trioxide aggregate (MTA) (control material) were used. The wettability, surface free energy (SFE), microporosity, nanoporosity and micro-gap size between the material and tooth root canal were evaluated. There was no difference in total SFE among tested cements (p<0.05), while CaSi+BaSO4, CaAl + SrCO3 and CaAl + SrF2 experienced superior wetting than other cements (p<0.05). The highest microporosity was observed in CaAl, whilst adding radiopacifiers into it decrease cements microporosity (p<0.05). The lowest nanoporosity was found for CaAl + ZrO2. The gap size was not statistically different among tested ceramics (p>0.05). Altogether, strontium containing radiopacyfiers result in improved microstructural characteristics of dental ceramics.